Bioreducible PEI-siRNA Nanocomplex for Liver Cancer Therapy: Transfection, Biodistribution, and Tumor Growth Inhibition In Vivo. (15th January 2013) - Xia, Wei; Li, Yan; Lou, Bo; Wang, Peijun; Gao, Xiaolong; Lin, Chao
Abstract : A bioreducible polyethylenimine (SS-PEI) was successfully applied as a nonviral carrier for the delivery of plasmid DNA and VEGF-siRNA in vitro and in vivo . The SS-PEI could strongly condense DNA or siRNA into nanosized complexes (below 200 nm) with positive surface charges. In vitro transfection experiments using GFP plasmid as gene reporter showed that the complexes of SS-PEI/DNA were able to efficiently transfect HepG2 cells, with efficiency comparable to that of polyethylenimine, a gold standard for nonviral gene delivery. Moreover, the complexes of SS-PEI/VEGF-siRNA could lead to reduced levels of VEGF protein in HepG2 cells in vitro . Treatment with the complexes of SS-PEI/VEGF-siRNA efficiently inhibited HepG2 tumor growth in an xenograft mouse model. The data of this study imply that the SS-PEI is a potent nucleic acid carrier applicable for liver cancer gene therapy.